Effects of gastrodin against carbon tetrachloride induced kidney inflammation and fibrosis in mice associated with the AMPK/Nrf2/HMGB1 pathway. Issue 5 (13th May 2020) - Ma, Jie-Qiong; Sun, Yun-Zhi; Ming, Qing-Lei; Tian, Zhi-Kai; Zhang, Yu-Jia; Liu, Chan-Min
Abstract : Gastrodin (GAS), the main phenolic glycoside extracted from Gastrodia elata Blume, exhibits potential renoprotective properties. Abstract : Gastrodin (GAS), the main phenolic glycoside extracted from Gastrodia elata Blume, exhibits potential renoprotective properties. Here, we examined the protective effects of GAS on carbon tetrachloride (CCl4 )-induced kidney inflammation and fibrosis in mice, and explored its underlying mechanisms. Our research findings revealed that GAS improved CCl4 -induced renal damage in mice. GAS inhibited kidney fibrosis and the deposition of collagen and α-smooth muscle actin (α-SMA). GAS suppressed CCl4 -induced inflammation in kidney tissue, as indicated by the decreased levels of proinflammatory cytokines, including tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6). The renoprotective effects of GAS were associated with inhibiting oxidative stress by regulating nuclear factor-erythroid 2-related factor 2 (Nrf2)-mediated antioxidant signaling and increasing adenosine 5′-monophosphate activated protein kinase (AMPK) activation. Furthermore, GAS supplementation inactivated the receptor for advanced glycation end products (RAGE) and the high-mobility group box-1 (HMGB1) pathway. GAS inhibited the activation of Toll-like receptors (TLRs), nuclear factor-kappa B (NF-κB) and transforming growth factor (TGF)-β. Collectively, this study clarified that GAS attenuates CCl4 -induced kidney inflammation and fibrosis via the AMPK/Nrf2/HMGB1 pathway.